Green initiatives in the maritime industry - Singapore's perspective - Chia, Kai Ling (2014)
Currently, the environmental impact of shipping is becoming the focal topic and environmental regulations are looking to become more stringent in the future. The shipping industry is therefore coming under growing pressure to improve their performance in terms of environmental protection. This would require collaboration of ship owners, operators, port side and maritime authority.